Ultra-thin 20 nm-PECVD-Si3N4 surface passivation in T-shaped gate InAlAs/InGaAs InP-based HEMTs and its impact on DC and RF performance. (September 2016) - Ding, Peng; Chen, Chen; Ding, Wuchang; Yang, Feng; Su, Yongbo; Wang, Dahai; Jin, Zhi
Highlights: Effect of surface passivation for InP-based HEMTs was studied using an ultra-thin 20 nm PECVD Si3 N4 layer. In DC performance, after passivation, its maximum transconductance ( gm, MAX ) is increased up to 1200 mS/mm. Verified by small-signal modeling, its Cgd after passivation can be effectively limited. S -parameter measurements demonstrate an increase in extracted fmax up to 450 GHz after passivation. Its RF performance can be improved in InP-based HEMTs by using an ultra-thin 20 nm Si3 N4 surface passivation. Abstract: Surface passivation in InP-based High Electron Mobility Transistors (HEMTs) plays an important role in reducing or eliminating their surface effects which limit both direct-current (DC) and radio-frequency (RF) performances. In the present work, effect of surface passivation was studied using an ultra-thin 20 nm PECVD Si3 N4 layer. In DC performance, after passivation, its maximum transconductance ( gm, MAX ) is increased up to 1200 mS/mm. It is found that, by scaling the thickness of Si3 N4 layer, the increase in Cgd after passivation can be effectively limited verified by small-signal modeling. As a result, S -parameter measurements demonstrate an increase in extracted fmax up to 450 GHz after passivation. The results show that, by using an ultra-thin Si3 N4 surface passivation, its RF performance can be improved in InP-based HEMTs.